Body phosphorus mobilization and deposition during lactation in dairy cows - Elizondo Salazar, Jorge Alberto (2012)
Dairy cow bone phosphorus (P) mobilization and deposition and their influence on P requirements were studied over the lactation cycle. Thirty Holsteins received a common diet during the dry period and one of the following three dietary treatments that varied in P percentage during the subsequent lactation (44 weeks): (i) 0.36 throughout (constant P, 0.36- 0.36-0.36), (ii) 0.36 for 30 weeks then 0.29 for 14 weeks (P changed once, 0.36-0.36-0.29), and (iii) 0.43 for 10 weeks, 0.36 for 20 weeks, and 0.29 for 14 weeks (P changed twice, 0.43-0.36-0.29). Six P balance studies were conducted during the experiment, including one during the dry period and five along lactation, based on P intake, faecal P, urinary P and milk P, when appropriate. Blood samples were taken during balance to analyse bone formation (osteocalcin) and resorption (pyridinoline) marker concentrations and rib biopsies performed to determine bone P content. Phosphorus balance was negative during weeks )4 to )1 relative to lactation for all groups and remained negative for cows fed 0.36% P during weeks 1–5, but showed a positive value for cows that received 0.43% P. The balance was close to zero for all groups at weeks 19–23 and showed a clear retention during weeks 38–42; by the end of lactation, cows re-stored most of the P mobilized earlier. The pattern in P balance was consistent with changes in blood bone metabolism marker concentrations, rib bone P content, and faecal and urinary P concentrations over the experiment, indicating that cows, irrespective of the dietary P treatments received, mobilized P from bone during the late dry period when fed a low-Ca diet and early lactation, and re-stored P in late lactation. This dynamic of P metabolism can have important implications for dietary P requirements and ration formulations.